An Effective Charger for Plug-In Hybrid Electric Vehicles (PHEV) with an Enhanced PFC Rectifier and ZVS-ZCS DC/DC High-Frequency Converter - G. Kanimozhi; L. Natrayan; S. Angalaeswari; Prabhu Paramasivam (Journal of Advanced Transportation)
A plug-in hybrid electric vehicles (PHEV) charger adapter consists of an AC/DC power factor correction (PFC) circuit accompanied by a full-bridge isolated DC/DC converter. This paper introduces an efficient two-stage charger topology with an improved PFC rectifier as front-end and a high-frequency zero voltage switching (ZVS). Current switching (ZCS) DC/DC converter is the second part. The front-end converter is chosen as bridgeless interleaved (BLIL) boost converter, as it provides the advantages like lessened input current ripple, capacitor voltage ripple, and electromagnetic interference. Resettable integrator (RI) control technique is employed for PFC and DC voltage regulation. The controller achieves nonlinear switching converter control and makes it more resilient with the faster transient response and input noise rejection. The second stage incorporates a resonant circuit, which helps in achieving ZVS/ZCS for inverter switches and rectifier diodes. PI controller with phase shift modulator is used for second-stage converter. It improves the overall efficacy of the charger by lowering the switching losses, lowering the voltage stress on the power semiconductor devices, and reversing recovery losses of the diodes. The simulations and experimental results infer that the overall charging efficiency increases to 96.5%, which is 3% higher than the conventional two-stage approach using the interleaved converter.